IL-6 in the Cerebrospinal Fluid Signals Disease Activity in Multiple Sclerosis - Stampanoni Bassi, Mario; Iezzi, Ennio; Drulovic, Jelena; Pekmezovic, Tatjana; Gilio, Luana; Furlan, Roberto; Finardi, Annamaria; Marfia, Girolama Alessandra; Sica, Francesco; Centonze, Diego; Buttari, Fabio (Frontiers in Cellular Neuroscience, 2020)
Specific proinflammatory and anti-inflammatory molecules could represent useful cerebrospinal fluid (CSF) biomarkers to predict the clinical course of multiple sclerosis (MS). The proinflammatory molecule interleukin (IL)-6 has been investigated in the pathophysiology of MS, and has been associated in previous, smaller studies to increased disability and disease activity. CSF IL-6 detectability in MS 2 This is a provisional file, not the final typeset article Here, we wanted to further address IL-6 as a possible CSF biomarker of MS by investigating its detectability in a large cohort of 534 MS patients and in 100 individuals with other non-inflammatory neurological diseases. In these newly diagnosed patients, we also explored correlations between IL-6 detectability, MS phenotypes and disease characteristics.We found that IL-6 was more frequently detectable in the CSF of MS patients compared with their control counterparts, as significant differences emerged between patients with clinically isolated syndrome, relapsing remitting, secondary progressive and primary progressive MS, compared to noninflammatory controls. IL-6 was equally present in the CSF of all MS phenotypes. In MS patients, IL-6 detectability was found to signal clinically and/or radiologically defined disease activity, among all other clinical characteristics.Our results add further evidence that CSF proinflammatory cytokines could be useful for the identification of those MS patients who are prone to increased prospective disease activity. In particular, IL-6 could represent an interesting prognostic biomarker of MS, as also demonstrated in other diseases where CSF IL-6 was found to identify patients with worse disease severity.